Spontaneous Descemet Membrane Detachment After Penetrating Keratoplasty—Clinical Presentation and Outcome of Air/Gas Descemetopexy. Issue 12 (December 2020) - Nahum, Yoav; Gal-Or, Orly; Dadon, Judith; Greenbaum, Aharon; Israeli, David; Melles, Gerrit R. J.; Bahar, Irit; Livny, Eitan
Abstract : Purpose: To describe the clinical characteristics and treatment of spontaneous Descemet membrane (DM) detachment occurring decades after penetrating keratoplasty (PK). Methods: A multicenter interventional case series design was used. We reviewed the medical records of 4 patients with a history of PK presenting with spontaneous DM detachment at 3 university hospitals in Israel and an ocular surgery institute in The Netherlands in 2016 to 2019. Patient demographic and clinical data, postoperative best corrected visual acuity, findings on preoperative and postoperative anterior segment optical coherence tomography (AS-OCT), and graft survival were recorded. Results: Patients were aged 46 to 50 years. All had undergone PK for keratoconus 20 to 26 years previously. Patients presented within 18 to 180 days of onset of visual disturbance. Symptoms included sudden painless visual loss (2 patients), gradual visual loss and foreign body sensation (1 patients), and visual loss not otherwise specified (1 patient). Slit-lamp examination showed corneal edema, and AS-OCT showed DM detachment of variable extent. In 2 patients, the initial diagnosis was graft rejection and failure. Treatment consisted of anterior chamber injection of air (n = 3) or 20% SF6 (n = 1). In 3 patients, the DM reattached and the cornea regained its clarity. The fourth patient had persistent DM detachment that required repeated PK. Conclusions: Spontaneous DM detachment can mimic late graft failure in patients after PK. If diagnosed early, DM reattachment may be performed by air/gas injection, avoiding repeated keratoplasty. Eyes with presumed late penetrating graft rejection or failure should be examined by AS-OCT to exclude DM detachment.